Pengaruh Komunikasi dan Budaya Organisasi terhadap Kinerja Karyawan PT. Bank Pembangunan Daerah Kalimantan Selatan Wilayah Banjarmasin - Rudy Fahrurazi; Saladin Ghalib; Hasanur Arifin (Universitas Lambung Mangkurat, 2014)
This research aimed to determine the influence of communication and organizational culture to increase employee performance. Organizational culture contains norms and values beliefs that guide the behavior of employees. Therefore, the company should have to provide a vehicle for employees to internalize the culture so that they are able to apply them in work.The research have been conducted at PT. Bank Pembangunan Daerah Kalimantan Selatan in the area of Banjarmasin. The method used a quantitative approach with a population of some 90 officials who have a Risk Management Certificate, using the survey method obtained sample size of 90 people. Data analysis using statistical techniques and a multiple linear regression to test the significant level using a t test with SPSS.The conclusion of this research is that communication and organizational culture variables have positive and significant impact on employee performance. Organizational cultural variables have the greatest influence to increase employee performance than other variables, with a regression coefficient of 0.437 or 43.7%.